Understanding the Implementation of the Health Personnel Professional Competency Test; A Juridical Review - Gunawan Widjaja (Science Midwifery, 2022)
This study intends to conduct a juridical investigation of the regulation of the Professional Competency Test for health workers as regulated in various kinds of legislation today. As a normative study, this research uses a normative juridical method. The data used as a study is secondary data, focusing on various provisions governing Competency Tests, in general, and explicitly regulating the Competency Tests of health workers' professions. Data analysis was carried out qualitatively to assess the meaning of the existing legal rules. This descriptive-analytical research aims to provide an overview of the overall setting of the Competency Test. Furthermore, this study analyzed the purpose of implementing the Competency Test for health professionals. The application of general legal principles is also carried out in order to obtain optimum results. The study results indicate the need for a redefinition of the purpose of the National Competency Test, which can be applied to all health workers.